2017
DOI: 10.1021/acs.langmuir.7b02404
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology of Epithelial Sodium Channel (ENaC) Embedded in Supported Lipid Bilayer Using a Single Nanopore Chip

Abstract: Nanopore-based technologies are highly adaptable supports for developing label-free sensor chips to characterize lipid bilayers, membrane proteins, and nucleotides. We utilized a single nanopore chip to study the electrophysiology of the epithelial Na channel (ENaC) incorporated in supported lipid membrane (SLM). An isolated nanopore was developed inside the silicon cavity followed by fusing large unilamellar vesicles (LUVs) of DPPS (1,2-dipalmitoyl-sn-glycero-3-phosphoserine) and DPPE (1,2-dipalmitoyl-sn-glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…Moreover, force–distance curves indicated that the POPC/Chol bilayers were slightly thicker upon the increasing of cholesterol content, ranging from 4.0 to 5.5 nm (increasing approximately 1.0 nm) (Figure 1). These values are comparable to the thickness of supported lipid bilayers previously determined by AFM [29,30]. As previous studies state, the interplay between cholesterol and phospholipid molecules promotes lateral ordering of lipid acyl chain leading to a lipid phase change from l d phase to l o phase [31,32,33].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, force–distance curves indicated that the POPC/Chol bilayers were slightly thicker upon the increasing of cholesterol content, ranging from 4.0 to 5.5 nm (increasing approximately 1.0 nm) (Figure 1). These values are comparable to the thickness of supported lipid bilayers previously determined by AFM [29,30]. As previous studies state, the interplay between cholesterol and phospholipid molecules promotes lateral ordering of lipid acyl chain leading to a lipid phase change from l d phase to l o phase [31,32,33].…”
Section: Discussionsupporting
confidence: 85%
“…The permeabiltization of cell membrane would increase when the external field was applied, which would lead to bacterial lysis and death. In our C 4 D system, the measured current through the media in the capillary was less than 1 μA at the excitation of 25 Vpp, though the voltage was larger than the one used in electric double layer [52,53,54]. The maximum conductivity of the media was 0.286 mS/cm measured by METTLER TOLEDOLE 740 (METTLER TOLEDO, Shanghai, China), that is, the resistivity is 416.7 Ω·cm.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, they used AFM to characterize the presence and thickness of supported lipid membrane (SLM) on the nanopore chip in another functionality measurement of SLM. It follows that AFM can be a useful tool for functionality characterization of biological membranes [ 76 ].…”
Section: Friction Measurement By Afmmentioning
confidence: 99%